2011
DOI: 10.1007/s10900-011-9356-8
|View full text |Cite
|
Sign up to set email alerts
|

Testing an Empowerment Intervention to Help Parents Make Homes Smoke-free: A Randomized Controlled Trial

Abstract: The objective of this randomized controlled trial was to test if parents' participation in an intervention based on an empowerment ideology and participatory experiences decreased the number of cigarettes smoked in homes. Sixty families were randomized to the intervention (n = 30) or control (n = 30) group. The intervention included three weekly group sessions followed by three weekly follow-up telephone calls over six consecutive weeks. During group sessions, parents shared experiences about environmental tob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 33 publications
0
22
0
1
Order By: Relevance
“…Seventy-five full-text articles were read. Forty-five studies were excluded for the following reasons: no relevant outcomes, 18 studies [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] ; the trial did not include a control group, 7 studies [56][57][58][59][60][61][62] ; the interventions were not aimed at parents of young children, 3 studies [63][64][65] ; the reporting period was ,1 month, 2 studies 66,67 ; data necessary for analysis were missing, 10 studies [68][69][70][71][72][73][74][75][76][77] ; the paper was a review article, 1 study 78 ; the article was a protocol, 2 studies 79,80 ; the article was a follow-up of a previous study, 1 study 81 ; there was no true control group (eg, 2 active interventions were compared), 1 study 82 .…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Seventy-five full-text articles were read. Forty-five studies were excluded for the following reasons: no relevant outcomes, 18 studies [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] ; the trial did not include a control group, 7 studies [56][57][58][59][60][61][62] ; the interventions were not aimed at parents of young children, 3 studies [63][64][65] ; the reporting period was ,1 month, 2 studies 66,67 ; data necessary for analysis were missing, 10 studies [68][69][70][71][72][73][74][75][76][77] ; the paper was a review article, 1 study 78 ; the article was a protocol, 2 studies 79,80 ; the article was a follow-up of a previous study, 1 study 81 ; there was no true control group (eg, 2 active interventions were compared), 1 study 82 .…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Of the 35 studies, twenty were identified by the parallel review and excluded [ 37 41 , 43 , 45 , 48 , 50 – 54 , 58 61 , 66 , 68 , 69 ]. All but one of these [ 53 ] were found and excluded by Rosen.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 15 studies which were excluded by Rosen at the stage of full-text reading, 6 were excluded because there were no relevant outcomes. (Chan [ 38 ], Curry [ 41 ], Emmons [ 45 ], Hughes [ 50 ], Ralston 2008 [ 58 ], Winickoff [ 68 ]) Six studies were excluded because data necessary for meta-analysis review was missing [ 39 , 48 , 51 , 52 , 61 , 69 ]. All but one of these [ 61 ] were missing means, and/or standard deviations, and/or sample sizes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One school-based study (Blanch et al, 2013) and one family-based study (Herbert et al, 2011) failed to detect a difference between the intervention and control groups. On the other hand, two hospital-based studies (Harutyunyan :http://dx.doi.org/10.7314/APJCP.2016.17.3.1235School-Based Intervention for Household Members towards a Smoke-Free Home: a Cluster Controlled Trial et al, 2013Yilmaz et al, 2013) and one family-based study (Kegler et al, 2015) reported significant effects of their interventions aiming to promote a SFH.…”
Section: Discussionmentioning
confidence: 99%